2016
DOI: 10.4274/jcrpe.2687
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Function and Thyroid Autoimmunity in Relation to Weight Status and Cardiovascular Risk Factors in Children and Adolescents: A Population-Based Study

Abstract: Objective: In obese subjects, slight increases have been observed in thyrotropin [thyroid-stimulating hormone (TSH)] levels, but data in children are scarce. The aim of this study was to evaluate whether thyroid function and autoimmunity vary with weight status in a healthy population of children and adolescents and to determine whether hyperthyrotropinemia is associated with any cardiovascular risk factor.Methods: This cross-sectional epidemiological study was conducted in Almería (Spain) on a representative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 39 publications
0
16
0
Order By: Relevance
“…While TSH in children has been found to be positively correlated with total cholesterol and non‐HDL cholesterol levels in some studies, others have not found any such relationship . The studies that have examined the relationship between mild SCH defined as TSH between 5 and 10 mIU/L and lipids in children have included only a small number of subjects .…”
Section: Discussionmentioning
confidence: 99%
“…While TSH in children has been found to be positively correlated with total cholesterol and non‐HDL cholesterol levels in some studies, others have not found any such relationship . The studies that have examined the relationship between mild SCH defined as TSH between 5 and 10 mIU/L and lipids in children have included only a small number of subjects .…”
Section: Discussionmentioning
confidence: 99%
“…When studying thyroid autoimmunity in children from the general population, frequencies vary between 0.4 and 3.7% in 8.8-12-year-old children, depending on population and which autoantibody that was tested [28][29][30]. In a study screening for thyroid autoimmunity and coeliac disease in 12-year-old Swedish children, 2.8% were tested positive for TPOAb in the healthy control group [30].…”
Section: Discussionmentioning
confidence: 99%
“…The influence of obesity on thyroid dysfunction, such as hypothyroidism has been studied in several epidemiological studies in Western countries (Rimm et al, 1975 ; Asvold et al, 2009 ; Gopinath et al, 2010 ; Marzullo et al, 2010 ; Ittermann et al, 2013 ; Garcia-Garcia et al, 2016 ). Some studies found that obesity could increase risk of hypothyroidism (Rimm et al, 1975 ; Asvold et al, 2009 ; Gopinath et al, 2010 ; Marzullo et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%